The relationship of rheological properties and the performance of silk fibroin hydrogels in tissue engineering application. (February 2023) - Elango, Jeevithan; Lijnev, Artiom; Zamora-Ledezma, Camilo; Alexis, Frank; Wu, Wenhui; Marín, José Manuel Granero; Sanchez de Val, Jose Eduardo Mate
Abstract: Hydrogel-based systems are widely used for conventional 3D-cell culture, where cells can be seeded on or embedded in 3D-matrix gels for cultivation. Several new approaches have emerged to develop innovative more performing polymeric biomaterials for tissue regeneration. Within this class of biomaterials, land and marine based-polymers (including among other collagens, silk, chitosan/chitin and alginates) have been explored to date. The best-known example of silk to date is the fiber produced by land-based animals like silkworms for the production of their cocoon. There are many successful studies already proving the empirical evidence of biomaterials from land-based silk in biomedical applications. Generally, silk-based hydrogels are mainly involved in the fabrication of different implants for skin, bone, cartilage and vascular-regeneration. The ideal silk fibroin hydrogels for skin, cosmetic and wound healing purposes should exhibit enhanced biological response which is mainly regulated by its tailored mechanical, rheological, viscoelastic properties, effective tissue regeneration ability, controllable swelling, hemostasis and biocompatibility. Accordingly, this review summarizes the rheological and viscoelastic properties of silk-fibroin based composite hydrogels obtained from various raw materials/composites, highlighting the relation of its rheological response to hydrogel biomaterial functions aiming biomedical applications. Highlights: Fibroin hydrogel should fabricated with δ < 1 viscoelastic value. The viscosity (1–2 % fibroin) with < 1 Pa could be optimal for fibroin hydrogel. Optimum gel strength and gelation time are 0.5–1.0 MPa and 20–45 min, respectively. The optimum swelling properties of fibroin hydrogel are 10–20 %.